2019
DOI: 10.1177/2515245918811301
|View full text |Cite
|
Sign up to set email alerts
|

Do Policy Statements on Media Effects Faithfully Represent the Science?

Abstract: Professional scientific groups such as the American Psychological Association (APA), American Academy of Pediatrics (AAP), and American Medical Association often release public statements (collectively called policy statements here) that speak to the current nature of science. Such statements may be intended to provide information for policymakers, inform the general public, inform clinical practice, or simply set the agenda for the group itself. Given that such statements speak to science, they may be assumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 58 publications
0
17
1
Order By: Relevance
“…There are also continuing concerns about publication bias, particularly in experimental studies (Hilgard, Engelhardt, & Rouder, 2017). Furthermore, the American Psychological Association has concluded that video games influence aggression but not violence (Calvert et al, 2017), although this report has itself come under critical scrutiny by outside scholars (Elson et al, 2019). Prescott et al (2018) and Anderson et al (2010) did find correlations between self-reports of aggressive behavior and VVGs over time, although the magnitude of such correlations are very small.…”
Section: Resultsmentioning
confidence: 99%
“…There are also continuing concerns about publication bias, particularly in experimental studies (Hilgard, Engelhardt, & Rouder, 2017). Furthermore, the American Psychological Association has concluded that video games influence aggression but not violence (Calvert et al, 2017), although this report has itself come under critical scrutiny by outside scholars (Elson et al, 2019). Prescott et al (2018) and Anderson et al (2010) did find correlations between self-reports of aggressive behavior and VVGs over time, although the magnitude of such correlations are very small.…”
Section: Resultsmentioning
confidence: 99%
“…To increase public trust in their findings, scientists have an obligation to work as transparently as possible, particularly when they collaborate with industry (Aczel et al, 2019). Greater transparency will provide a valuable tool for informing policy (Elson et al, 2019) and the heated academic debates that surround the global health impacts of games.…”
Section: Video Game Behaviourmentioning
confidence: 99%
“…To increase public trust in their findings, scientists have an obligation to work as transparently as possible, particularly when they collaborate with industry [ 36 ]. Greater transparency will provide a valuable tool for informing policy [ 37 ] and the heated academic debates that surround the global health impacts of games.…”
Section: Introductionmentioning
confidence: 99%